Sosialisasi Pentingnya Pencatatan Laporan Keuangan Sederhana Pada Usaha Kuliner Ikan Bakar Laut Timur Dan Sei Babi Kupang - Emerenciana Hoar Seran; Ratri Paramitalaksmi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Financial reports are records of financial information from a company in an accounting period. The existence of financial reports that can be used to describe company performance, especially in the financial sector. The purpose of financial reports is to provide information about the financial position and cash flows of an entity that is useful for the majority of users of financial reports in making economic decisions. The culinary business of Timor Sea grilled fish and kupang sei pork is one of the businesses operating in the culinary business sector. Since this business was built, the Timor Sea Grilled Fish and Kupang Sei Pork culinary business has not recorded financial reports so that sometimes errors occur in detailing the income and expenses of the business.